EFEKTIVITAS CANGKANG BUAH PALA (Myristica fragrans) SEBAGAI KARBON AKTIF DALAM PENGOLAHAN AIR LIMBAH DOMESTIK - Calvin Ronaldo Lekatompessy; Rofiq Sunaryanto; Nurhayati (FT-USNI, 2022)
Activated carbon is a material that contains high carbon elements and has a porous solid. The material used in this research is a nutmeg shell. The purpose of this study was to determine the effectiveness of activated charcoal from the shell of nutmeg (Myristica fragrans) as activated carbon in treating domestic wastewater. The variables studied to compare the effect of the wastewater absorption process are the concentration of the chemical NaOH 15% with temperature variations of 400ºC, 450ºC, and 500ºC. The best activation results were obtained at a temperature of 450ºC with a water content of 4.22%, an ash content of 10.24%, and iodinecontent of 577,395 mg/g. Activated charcoal parameters refer to SNI 06-3730-1995 regarding the quality standard requirements for activated charcoal. Wastewater management by activated charcoal from the shell of nutmeg (Myristica fragrans) with a concentration of 10, 15, 20 grams of activated charcoal. The best results were obtained by the concentration of activated charcoal 20 grams with a pH value of 9.0, TSS 0.663 mg/L, BOD 7.3 mg/L. For pH parameters, the effectiveness of activated charcoal is less than the maximum, and it does not meet quality standards.